Digitalization of Marketing, Finance and Inventory Management in MSMEs “Sriti Gamplong” - Audita Nuvriasari; Bhakti, Listiana; Fadhila, Annisa Nur; Asmarani, Widya Puspita; Pramudian, Achmad Fajri; Raihan, Muhammad (Asian Journal of Community Services, 2024)
This community service activity is carried out by the MSMEs "Sriti Gamplong" which produces various handicrafts. The aim of this activity is to optimize marketing activities by utilizing digital technology such as: social media and marketplaces. It is hoped that this will increase consumer buying interest. Apart from that, technology-based ways of managing finances and inventory were also introduced. The results of the activity show that partners increasingly understand the importance of digitalization to support increased business performance. Apart from that, marketing activities are becoming more effective, financial and inventory management is becoming more controlled.